Inovasi Sistem Pembelajaran Masa Pandemi COVID-19 Pada Pendidikan Anak Usia Dini Di RA Hibah - Nazila Adistiarachma; Purwati Purwati (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2022)
The global covid-19 pandemic has had far-reaching effects on education as well. Whole education, including early childhood education, makes it impossible to engage in face-to-face teaching, so an innovation of learning systems is needed to hold it. Contrary to current circumstances, some schools already carry out face-to-face learning but with strict health protocols. So RA Hibah has carried out face-to-face study with health protocol. Thus, the study is carried out with a view to discovering the innovation of the different learning systems that RA Hibah made during the pandemic, since the pandemic is not over and so the study is carried out according to conditions. Research methods use qualitative research methods, with data collection techniques of observation, interviews, and literature studies. Observations and interviews have found that innovation in learning systems during pandemics in RA Hibah, which is online learning, rolling learning, and offline learning. Keywords: Innovation Learning Systems, Early Childhood, Covid-19 Pandemic References Ananda, R. (2017). Implementasi Nilai-nilai Moral dan Agama pada Anak Usia Dini. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 1(1), 19–31. https://doi.org/10.31004/obsesi.v1i1.28 Anggraini, V., Yulsyofriend, Y., & Yeni, I. (2019). Stimulasi Perkembangan Bahasa Anak Usia Dini Melalui Lagu Kreasi Minangkabau Pada Anak Usia Dini. Pedagogi : Jurnal Anak Usia Dini dan Pendidikan Anak Usia Dini, 5(2), 73–84. https://doi.org/10.30651/pedagogi.v5i2.3377 Aprily, N. M., Rizqi, A. M., & Purwati, P. (2021). Cageur Bageur Bener Pinter Singer: Filosofi Pengasuhan Sunda Dalam Pendidikan Karakter Di Raudhatul Athfal (Ra). JIV-Jurnal Ilmiah Visi, 16(1), 11–24. https://doi.org/10.21009/jiv.1601.2 Ariyanti, T. (2016). Pentingnya Pendidikan Anak Usia Dini Bagi Tumbuh Kembang Anak. Jurnal Dinamika Pendidikan Dasar, 8(1), 50–58. Azizah, N., & Dewi, A. C. (2021). Analisis Perkembangan Bahasa Semantik Dan Sintaksis Anak Dalam Kegiatan Belajar Dari Rumah. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 6(2), 139–146. Dewi, A. R. T., Mayasarokh, M., & Gustiana, E. (2020). Perilaku Sosial Emosional Anak Usia Dini. Jurnal Golden Age, 4(01), 181–190. https://doi.org/10.29408/jga.v4i01.2233 Faiz, A., Robby, S. K. I., Purwati, & Fadilla, R. N. (2021). Penanaman Nilai-nila Religius pada Orang Tua Siswa di Sekolah Dasar. Jurnal basicedu, 5(6), 5853–5858. Faiz, A., Soleh, B., Kurniawaty, I., & Purwati, P. (2021). Tinjauan Analisis Krisis Terhadap Faktor Penghambat Pendidikan Karakter di Indonesia. Jurnal Basicedu, 5(4), 1766–1777. Fitrah, & Luthfiyah. (2017). Metodologi Penelitian (Ruslan & M. M. Efendi (ed.)). CV Jejak. Fitri, E. A., Saparahayuningsih, S., & Agustriana, N. (2017). Perencanaan Pembelajaran Kurikulum 2013 Pendidikan Anak Usia Dini. Jurnal Ilmiah POTENSIA, 2(1), 1–13. https://doi.org/10.33369/jip.2.1 Fitriani, R., & Adawiyah, R. (2018). Perkembangan Fisik Motorik Anak Usia Dini. Jurnal Golden Age, 2(01), 25–34. https://doi.org/10.29408/ goldenage.v2i01.742 Harianja, S. (2022). Pelaksanaan Kegiatan iHT Dengan Aplikasi Google Meeting Untuk Meningkatkan Kemampuan Guru Menyusun RPP Daring Masa Pandemi COVID 19. Nuansa Akademik: Jurnal Pembangunan Masyarakat, 7(1), 1–12. https://doi.org/10.47200/JNAJPM.V7I1.956 Herliandry, L. D., Nurhasanah, Suban, M. E., & Kuswanto, H. (2020). Pembelajaran Pada Masa Pandemi Covid-19. Jurnal Teknologi Pendidikan, 22(1), 65–70. Hidayat, F., Hidayat, I., Ghofur, A., & Setiawan Santoso, F. (2021). Penanganan Kesehatan Pasien Reaktif COVID-19 Melalui Terapi Zikir Dan Lingkungan Wawasan Pengalaman Subyektif. Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 11(1), 1–12. https://doi.org/10.47200/ ULUMUDDIN.V11I1.424 Husna, M., & Sugito, S. (2021). Eksplorasi Penerapan Pembelajaran Tatap Muka Terbatas pada Jenjang PAUD di Masa Kebiasaan Baru. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 6(3), 1846–1858. https://doi.org/10.31004/obsesi.v6i3.1814 Iriansyah, H. S. (2020). Membangun Kreativitas Guru dengan Inovasi Pembelajaran di Masa Pandemi Covid-19. Prosiding Seminar Nasional Pendidikan STKIP Kusuma Negara II, 1, 1–6. Khasanah, D. R. A. U., Pramudibyanto, H., & Widuroyekti, B. (2020). Pendidikan Dalam Masa Pandemi Covid-19. Jurnal Sinestesia, 10(1), 41–48. Lia, L., Rakhmat, C., & Nugraha, F. (2021). Analisis Pembelajaran Pendidikan Karakter Disiplin Di Sd Negeri Negla. PIWURUK: Jurnal Sekolah Dasar, 1(1), 33–44. https://doi.org/10.36423/pjsd.v1i1.641 Maryanti, D., Rakhmat, C., & Hodidjah. (2014). Pendidikan keluarga dalam meningkatkan prestasi belajar siswa kelas vi sdn i muncang kecamatan sodonghilir kabupaten tasikmalaya. Pedadidaktika, 1(2), 30–37. Nasution, N., Yaswinda, Y., & Maulana, I. (2020). Analisis Pembelajaran Berhitung melalui Media Prisma Pintar pada Anak Usia Dini. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 4(1), 230–236. https://doi.org/10.31004/obsesi.v4i1.311 Norhikmah, N., Rizky, N. F., Puspita, D., & Saudah, S. (2022). Inovasi Pembelajaran dimasa Pendemi: Implementasi Pembelajaran berbasis Proyek Pendekatan Destinasi Imajinasi. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 6(5), 3901–3910. https://doi.org/10.31004/ obsesi.v6i5.1886 Novitasari, Y. (2018). Analisis Permasalahan "Perkembangan Kognitif Anak Usia Dini”. PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2(01), 82–90. https://doi.org/10.31849/paudlectura.v2i01.2007 Nurhayati, R. (2020). Analisis SWOT Pelaksanaan Perkuliahan Daring Pada Masa Pandemi COVID-19 di STAI Yogyakarta. Nuansa Akademik: Jurnal Pembangunan Masyarakat, 5(1), 63–72. https://doi.org/10.47200/ JNAJPM.V5I1.916 Nurwita, S. (2020). Meningkatkan Perkembangan Seni Anak Menggunakan Media Smart Hafiz Di Paud Aiza Kabupaten Kepahiang. Early Childhood Research and Practice, 1(01), 34–37. https://doi.org/10.33258/ ecrp.v1i01.1070 Nuryati, N., Muthmainnah, M., Lubis, H. Z., Talango, S. R., Ibrohim, B., & Nadjih, D. (2021). Metode Role Playing Dalam Meningkatkan Motivasi Berprestasi Anak Usia Dini Selama Masa Learning From Home. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 6(2), 139–148. https://doi.org/10.32678/AS-SIBYAN.V6I2.4649 Pertiwi, L. K., Febiyanti, A., & Rachmawati, Y. (2021). Keterlibatan Orang Tua Terhadap Pembelajaran Daring Anak Usia Dini Pada Masa Pandemi Covid-19. Cakrawala Dini: Jurnal Pendidikan Anak Usia Dini, 12(1), 19–30. https://doi.org/10.17509/cd.v12i1.26702 Pratama, R. E., & Mulyati, S. (2020). Pembelajaran Daring dan Luring pada Masa Pandemi Covid-19. Gagasan Pendidikan Indonesia, 1(2), 49–59. https://doi.org/10.30870/gpi.v1i2.9405 Putri, R. N. (2020). Indonesia dalam Menghadapi Pandemi Covid-19. Jurnal Ilmiah Universitas Batanghari Jambi, 20(2), 705–709. https://doi.org/10.33087/ jiubj.v20i2.1010 Rosita, T., Rakhmat, C., & Soendari, T. (2020). Peran Interaksi Orangtua Pada Keterampilan Sosial Siswa Sekolah Dasar Yang Memiliki Hambatan Adhd. Journal of Elementary Education, 03(03), 82–90. Rusniah, R. (2017). Meningkatkan Perkembangan Bahasa Indonesia Anak Usia Dini Melalui Penggunaan Metode Bercerita Pada Kelompok a Di Tk Malahayati Neuhen Tahun Pelajaran 2015/2016. JURNAL EDUKASI: Jurnal Bimbingan Konseling, 3(1), 114–130. https://doi.org/10.22373/ je.v3i1.1445 Sujiono, Y. N. (2013). Konsep Dasar Pendidikan Anak Usia Dini (7 ed.). PT Indeks. Syamsiyah, N., & Hardiyana, A. (2021). Implementasi Metode Bercerita sebagai Alternatif Meningkatkan Perkembangan Bahasa Anak Usia Dini. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 6(3), 1197–1211. https://doi.org/10.31004/obsesi.v6i3.1751 Taznidaturrohmah, Y. E., Pramono, P., & Suryadi, S. (2020). Upaya meningkatkan kemampuan motorik halus melalui kegiatan montase pada anak kelompok B di TK Dharma Wanita Dinoyo 01 Mojokerto. Jurnal Pendidikan Anak, 9(1), 20–26. https://doi.org/10.21831/jpa.v9i1.29805